2007
DOI: 10.1002/cncr.22415
|View full text |Cite
|
Sign up to set email alerts
|

EphA2 overexpression is associated with angiogenesis in ovarian cancer

Abstract: Fiber connections of the general visceral sensory centers in the brainstem were studied with tract‐tracing methods in a percomorph teleost, tilapia Oreochromis niloticus. General visceral afferents of the vagal nerve from abdominal viscera terminated bilaterally in the commissural nucleus of Cajal (NCC) and area postrema (AP). The NCC and AP projected bilaterally to the secondary general visceral nucleus (SVN), four diencephalic nuclei (the preglomerular general visceral nucleus [pVN], nucleus of the lateral r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
94
1
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 103 publications
(101 citation statements)
references
References 124 publications
(183 reference statements)
5
94
1
1
Order By: Relevance
“…In both cases, there was a significant association between increased EphA2 expression in the tumor cells with increased microvessel density. Furthermore, Lin and colleagues reported that increases in EphA2 expression and microvessel density corresponded to a decrease in patient survival (Lin et al, 2007). These data suggest that the inability of aggressive melanoma cells lacking sufficient EphA2 to form tumors in mice may be due to impaired tumor neovascularization, especially given previous reports that firmly establish a role for EphA2 in mediating angiogenesis in conjunction with the inability of these cells to undergo VM in vitro.…”
Section: The Role Of Epha2 In Mediating Melanoma Tumor Cell Vasculogementioning
confidence: 88%
See 1 more Smart Citation
“…In both cases, there was a significant association between increased EphA2 expression in the tumor cells with increased microvessel density. Furthermore, Lin and colleagues reported that increases in EphA2 expression and microvessel density corresponded to a decrease in patient survival (Lin et al, 2007). These data suggest that the inability of aggressive melanoma cells lacking sufficient EphA2 to form tumors in mice may be due to impaired tumor neovascularization, especially given previous reports that firmly establish a role for EphA2 in mediating angiogenesis in conjunction with the inability of these cells to undergo VM in vitro.…”
Section: The Role Of Epha2 In Mediating Melanoma Tumor Cell Vasculogementioning
confidence: 88%
“…Recently, there have been reports attempting to investigate a correlation between EphA2 and microvessel density in both colorectal and ovarian carcinomas (Kataoka et al, 2004;Lin et al, 2007). In both cases, there was a significant association between increased EphA2 expression in the tumor cells with increased microvessel density.…”
Section: The Role Of Epha2 In Mediating Melanoma Tumor Cell Vasculogementioning
confidence: 99%
“…44 EphA2 has been also shown to promote tumorigenesis by enhancing angiogenesis. The effects on angiogenesis may be direct (EphA2 overexpression has been noted in angiogenic blood vessels and may contribute to vasculogenic mimicry) 18 or indirect (role in VEGF mediated angiogenesis). 45,46 In the present study, we found that EphA2 overexpression resulted in significantly increased tumor growth and microvessel density, suggesting that increased angiogenesis likely contributed to the greater tumor growth.…”
Section: © 2 0 0 8 L a N D E S B I O S C I E N C E D O N O T D I S mentioning
confidence: 99%
“…17 We have also demonstrated that increased EphA2 expression in ovarian cancer samples is strongly associated with critical factors involved in angiogenesis and invasion such as greater microvessel density and higher matrix metalloproteinase (MMP) expression. 18 Based on the high frequency of EphA2 overexpression and its association with aggressive tumor features, we and others have employed either agonist antibodies or in vivo siRNA to decrease EphA2 levels. Indeed, these approaches demonstrated decreased tumor growth and improved survival in orthotopic ovarian cancer mouse models.…”
Section: Introductionmentioning
confidence: 99%
“…41 Tumor MVD was calculated as the average CD31-positive vessel count over 5 sections under x200 high-power fields (HPF). A vessel was defined as an open lumen with 1 or more immediately adjacent CD31-positive cell(s).…”
Section: Cd31 Immunostainingmentioning
confidence: 99%